If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-2 + x) + -1(x + -4) = 0 (-2 * 2 + x * 2) + -1(x + -4) = 0 (-4 + 2x) + -1(x + -4) = 0 Reorder the terms: -4 + 2x + -1(-4 + x) = 0 -4 + 2x + (-4 * -1 + x * -1) = 0 -4 + 2x + (4 + -1x) = 0 Reorder the terms: -4 + 4 + 2x + -1x = 0 Combine like terms: -4 + 4 = 0 0 + 2x + -1x = 0 2x + -1x = 0 Combine like terms: 2x + -1x = 1x 1x = 0 Solving 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = 0 Simplifying x = 0
| (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 |